2020
DOI: 10.31234/osf.io/gvfsn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conceptual Relations Predict Colexification across Languages

Abstract: In natural language, multiple meanings often share a single word form, a phenomenon known as colexification. Some sets of meanings are more frequently colexified across languages than others, but the source of this variation is not well understood. We propose that cross-linguistic variation in colexification frequency is non-arbitrary and reflects a general principle of cognitive economy: More commonly colexified meanings across languages are those that require less cognitive effort to relate. To evaluate our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 13 publications
5
18
0
Order By: Relevance
“…Contributing to this lower alignment were cross-linguistic differences in word frequency, differences in semantic neighborhood densities, and differences in patterns of polysemy. 15,34,82 We observed highest semantic alignment in domains characterized by high internal structure: numbers, temporal terms, and kinship terms. This result suggests that the structure of e.g., a base-10 number system, a 12-month calendar -products of cultural evolution whose acquisition may require experience with language 83,84 -constrains semantic relationships among words like "five" and "ten", "month" and "year" in a very similar way in different languages.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Contributing to this lower alignment were cross-linguistic differences in word frequency, differences in semantic neighborhood densities, and differences in patterns of polysemy. 15,34,82 We observed highest semantic alignment in domains characterized by high internal structure: numbers, temporal terms, and kinship terms. This result suggests that the structure of e.g., a base-10 number system, a 12-month calendar -products of cultural evolution whose acquisition may require experience with language 83,84 -constrains semantic relationships among words like "five" and "ten", "month" and "year" in a very similar way in different languages.…”
Section: Discussionmentioning
confidence: 80%
“…13,14 Both perspectives likewise allow vocabularies to adapt to differences in communicative need. 15 To the extent that people in colder climates are more likely to need to distinguish between "ice" and "snow", we ought to find that languages spoken in colder climates are more likely to lexicalize this difference, and indeed we do, 16 see also. 4,[17][18][19] However, when it comes to common "everyday" meanings, the predictions of the universalist and relative perspectives diverge.…”
mentioning
confidence: 86%
“…5 Lexical ambiguity allows the mapping of multiple meanings to the same wordform and, in doing so, it enables the preferential re-use of short words (Piantadosi et al, 2012). Thus, the mapping of multiple meanings to the same form could be a source of efficiency in the lexicon (Fenk-Oczlon and Fenk, 2008;Ferrer-i-Cancho and Vitevitch, 2018;Casas et al, 2019;Trott and Bergen, 2020;Xu et al, 2020). Nonetheless, we do not treat it explicitly here.…”
Section: Words As Meaningsmentioning
confidence: 99%
“…For instance, Jr. and Xu (2019) developed a multi-modal semantic framework based on the exemplar model of chaining and showed that it predicts children's overextension behavior in a variety of studies from the psychological and linguistic literature. Xu et al (2020) showed that the frequency variation in cross-linguistic colexification, i.e., why certain senses are more commonly grouped (e.g., 'fire'-'flame') under a single word form than others (e.g., 'fire'-'anger') can be explained by a principle of cognitive economy, whereby senses that are frequently colexified across languages tend to be easily associable -an argument that is consistent with the chaining account presented here. However, critically lacking is demonstrating how the approaches and principles identified in language development and cross-linguistic settings can also explain historical semantic change attested in the world's languages.…”
Section: Toward a General Theory Of Word Meaning Extensionmentioning
confidence: 99%